Syphilis continues to retreat: nation sets sights on elimination cdc reports all-time syphilis lows and concent ration in 1% of u.s. Counties - DST (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Syphilis rates have declined an additional 19 percent in l 998 paving the way toward a nation’s goal of elimination. The national rate of 2.6 cases per 100.000 population, adrop from 3.2 cases in 1997, is the Jowest levei ever recorded, according to new data released today bay the Centers for Disease Control and Prevention (CDC). [...]